Tax Avoidance and Firm Performance: Empirical Evidence of Benefits and Risks of Company Tax Planning - Prinintha Nanda Soemarsono; Bani Alkausar; Wahyu Firmandani; Yanuar Nugroho; Heru Tjaraka (Universitas Muhammadiyah Malang, 2024)
Purpose: This study provides empirical evidence on how a company's efforts to avoid paying taxes through its tax planning strategy affect its performance. Methodology/approach: This study is explanatory research and uses samples of the companies listed in the Indonesia Stock Exchange (IDX) during the period 2015 to 2022 using a purposive sampling method. The analytical method used is the regression equation. Findings: The findings suggest that company carries out tax avoidance to streamline corporate tax payments to improve the company's financial performance. The company's actions in tax avoidance efforts have been proven to provide additional benefits for the company through the addition of cash flow. Practical and Theoretical contribution/Originality: This research contributes to theory and practice. First, this study provides empirical evidence of the agency theory regarding the efforts of company managers to meet investors' expectations through corporate tax planning strategies to maximize company’s financial performance. Second, this study guides companies in their efforts to implement tax planning, which positively impacts company performance by increasing company profits. Research Limitation: For further research, external factors that affect the company's financial performance can be added, such as political connections.